Poročilo o latenskodobnem naselju v Mannersdorfu an der March, Spodnja Avstrija - Kern, Anton (Arheološki vestnik, 1996)
Field observations and documentation at the site of Mannersdorf enable on the one hand an overview of the construction and arrangement of a Celtic lowland settlement, while the finds f r om a pottery kiln and individual structures enrich our knowledge of the high quality products of the local Celtic craftsmen of the 2nd and the beginning of the 1st centuries BC. The excavated settlement structures and other remains are part of a larger archaeological site, which extends (as documented by aerial photographs) more than 100 m. in length to the neighboring commune of Angern an der March. It can be suggested that the La Tene settlement has not yet been entirely explored and that it extends further to the south and west.